Novel Sulfur Metabolites of Garlic Attenuate Cardiac Hypertrophy and Remodeling through Induction of Na+/K+-ATPase Expression - Khatua, Tarak N.; Borkar, Roshan M.; Mohammed, Soheb A.; Dinda, Amit K.; Srinivas, R.; Banerjee, Sanjay K. (Frontiers in Pharmacology, 2017)
Epidemiologic studies show an inverse correlation between garlic consumption and progression of cardiovascular disease. However, the molecular basis for the beneficial effect of garlic on the heart is not known. Therefore, the objective of the present study was to 1) investigate the effect of raw garlic on isoproterenol-induced cardiac hypertrophy 2) find the active metabolites of garlic responsible for the beneficial effect. Cardiac hypertrophy was induced in-vivo in rat by subcutaneous single injection of isoproterenol 5 mg kg-1 day-1 for 15 days and the effect of garlic (250mg/kg/day orally) was evaluated. Garlic metabolites in in-vivo were identified by LC/MS study. The effect of garlic and all metabolites were evaluated against hypertrophy in H9C2 cells. Garlic normalized cardiac oxidative stress after isoproterenol administration. Cardiac pathology and mitochondrial enzyme activities were improved in hypertrophy heart after garlic administration. Decreased Na+/K+-ATPase protein level that observed in hypertrophy heart was increased after garlic administration. We identified three garlic metabolites in rat serum. To confirm the role of garlic metabolites on cardiac hypertrophy, Na+/K+-ATPase expression and intracellular calcium levels were measured after treating H9C2 cells with raw garlic and two of its active metabolites, allyl methyl sulfide and allyl methyl sulfoxide. Raw garlic and both metabolites increased Na+/K+-ATPase protein level and decreased intracellular calcium levels and cell size in isoproterenol-treated H9C2 cells. This antihypertrphic effect of garlic and its sulfur metabolites were lost in H9C2 cells in presence of Na+/K+-ATPase inhibitor. In conclusion, garlic and its active metabolites increased Na+/K+-ATPase in rat heart, and attenuated cardiac hypertrophy and associated remodeling. Our data suggest that identified new garlic metabolites may be useful for therapeutic intervention against cardiac hypertrophy.